Infantile epileptic spasms syndrome as a new phenotype in TOP2B deficiency caused by a de novo variant: a case report and literature review - Zhu, Guo-qin; Yao, Yao; Yang, Ling-yun; Hua, Ying; Li, Guo-min (Frontiers in Pediatrics, 2025)
Background: Type II DNA topoisomerases (EC5.99.1.3) are enzymes that catalyze topological changes during DNA replication and gene transcription in an ATP-dependent manner. Vertebrates have two isoforms: topoisomerase IIα and β. Type II topoisomerase β is encoded by TOP2B. For TOP2B, a number of germline pathogenic variants have been identified as causative for human diseases, including Hoffman syndrome, ablepharon-macrostomia syndrome with immunodeficiency, B-cell immunodeficiency, distal limb anomalies, and urogenital malformations syndrome. To date, only 14 patients with the above diseases from seven families have been reported in PubMed. Herein, we describe an additional case of a child who presented with “infantile epileptic spasms syndrome” (IESS) as the first symptom, B-cell immunodeficiency, dysmorphic facial features, and a pathogenic variant in TOP2B. The c.1901A > G variant in TOP2B is new to our study, which further enriches the genotype of TOP2B deficiency. Our patient manifested as a typical triad: infantile spasms, hypsarrhythmia on electroencephalogram, and developmental arrest at the age of 7 months. Although epilepsy and neurodevelopmental disorders have been reported in patients with TOP2B deficiency, typical IESS has not been described previously. IESS in our patient further expands the phenotype of TOP2B. The patient was started on monthly intravenous immunoglobulin replacement therapy after being diagnosed with TOP2B deficiency and since then has not suffered from severe infections. TOP2B deficiency is a group of heterogeneous diseases, which is ultrarare. The results from our study extend the phenotype and genotype spectrum of TOP2B deficiency. TOP2B may be a causative gene for IESS.